Incidental bladder wall alteration as a surgical complication risk factor in Indonesian benign prostate hyperplasia patient - Daniel Mahendra Krisna; Akhada Maulana; Erwin Kresnoadi (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2020)
Bladder obstruction due to benign prostatic hyperplasia (BPH) causes bladder walls alteration such as trabecular and diverticula. Although it is asymptomatic, however it affects the surgery complication. The aim of this study was to evaluate the correlation between bladder wall alteration and post-surgery complications in BPH patients. It was a descriptive observational study with cross-sectional design involving BPH patients who underwent histopathological examination and surgical intervention in the Bhayangkara Hospital Mataram from January 2010-December 2014. Data of the patients including age, place of birth, intraoperative finding, comorbid condition, and post-surgery complication were obtained from the medical record. The relationship between variables was analyzed using Pearson correlation test and linear regression test.A total 114 subjects were involved in this study with the most common age was in the range 60-69 years (43.0%). Seventy-fivesubjects (74.3%) had trans urethra resection of prostate (TURP). Trabecula (28.7%), diverticula (4.0%), and bladder stone (10.9%) were found when the surgical intervention performed. The most common post-surgical complication was chip or clot retention (56.4%). Significantly relationship betweenintraoperative finding with post-surgical complication was observed (r= 0.265; R2 = 0.07; p<0.05). In conclusion, there is correlation between bladder wall alteration and post-surgicalcomplication in BPH patients. Early bladder wall alteration screening is suggested in BPH patients before surgical intervention performed.